Surface morphology, phase structure and property evolution of anodized titanium during water vapor exposure - Chen, Zhaoxiang (2016)
The effects of water vapor exposure on surface characteristics of anodized titanium were investigated. The anodized titanium was prepared in 1 M phosphoric acid solution at 170 V. The as-prepared TiO2 layer consisted of amorphous oxides and exhibited a porous microstructure with many craters on the surface. Exposure to water vapor at 160 °C caused the TiO2 layer to undergo significant surface morphology evolution and phase transition. Specifically, after the initial exposure, many oxide microspheres emerged on the surface of anodized titanium. Then, these microspheres grew continuously at the expense of amorphous oxides and coalesced with one another. The X-ray diffraction and Raman spectroscopy analyses indicated that the exposure transformed amorphous oxides into crystalline anatase. The surface property investigation of anodized titanium showed that the adhesion strength of anodic TiO2 layer decreased significantly after the exposure.